EFEKTIVITAS PENGGUNAAN METODE EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA PADA MATERI TITRASI ASAM BASA - Rendy Renaldy Pikoli; Rustam Musta; La Harimu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Chemistry learning not only requires students to understand concepts theoretically but also emphasizes scientific skills through laboratory activities. However, student's science process skills and learning outcomes in acid–base titration remain relatively low. Therefore, a teaching method that actively involves students in the learning process is needed. This study aimed to determine the effectiveness of the experimental method on student's science process skills and learning outcomes in acid–base titration at SMA Negeri 4 Konawe Selatan. This study employed a quantitative approach using a pre-experimental method with a One-Group Pretest– Posttest Design. The sample consisted of 25 twelfth-grade students from Class XII A of SMA Negeri 4 Konawe Selatan. The research instruments included a science process skills observation sheet, a learning outcomes test, and a student response questionnaire. The data were analyzed using descriptive statistics and n-Gain analysis. The results showed that the implementation of the experimental method had a positive effect on student's science process skills and learning outcomes. The mean science process skills score was 71.14, which was categorized as very good. Student’s learning outcomes improved from a mean pretest score of 45.60 to a mean posttest score of 83.80, with a mean n-Gain score of 0.71, which was categorized as high. In addition, student’s responses to the implementation of the experimental method obtained an average percentage of 83.53, which was classified as very good. Based on these findings, it can be concluded that the experimental method is effective for teaching acid–base titration in chemistry because it improves student’s science process skills and learning outcomes.